EKSPLORASI PRAKTIK DAN PEMAKNAAN CALON GURU SEKOLAH DASAR TERHADAP EVALUASI HOLISTIK BERBASIS KECERDASAN MAJEMUK - Nurhudayah Manjani; Muhammad Takwin Machmud; Syahrial; Muhammad Iklhas (Universitas Negeri Medan, 2025)
This study explores pre-service elementary teachers’ understanding and practice of holistic assessment based on multiple intelligences. Using a qualitative case study with phenomenological elements, 20 sixth-semester students from Universitas Negeri Medan were purposively selected. Data were collected through observations, semi-structured interviews, document analysis, and reflective journals, validated via triangulation and member checking. Findings indicate that while students possess strong theoretical knowledge of multiple intelligence domains, their practice often shows inconsistencies, including misclassification of cognitive levels, reliance on visual complexity, and replication of conventional test formats. The use of AI also affects assessment accuracy. Results highlight the need for teacher education to strengthen assessment literacy, integrating cognitive analysis and multiple intelligences, alongside AI literacy, to produce valid, holistic instruments that genuinely demand higher-order thinking. This study reveals a persistent gap between theory and practice in preparing teachers for holistic mathematics assessment.